The cost benefits and potential drawbacks of the “Leaning Against the Wind’’ approach in terms of increasing Effectiveness of Macro-prudential Policy for preventing financial crisis and promoting financial stability - DINAR , BRAHIM; AKRAM , EL FANTAROUSSI; SEBTI, OTMANE (Revue Internationale des Sciences de Gestion, 2024)
We study in this paper the benefits of adopting the approach of LAW (Leaning Against the Wind) in monetary policy amid Central banks especially in the context of Macroprudential policy to prevent any systemic risk tending to impact financial stability, we also demonstrate the potential limits and disadvantages of the LAW approach for certain cases, the study investigates whether the approach is wisdom enough to be considered in monetary policy that reacts to perceive financial imbalances such as excess credit growth. This research paper will also demonstrate the vital role and the main target of adopting a strong macro-prudential policy by central banks and how it can prevent financial crisis and systemic risks.